External Shocks, Cost Push and Stagflation in Iran - Seyyed Ahmad Reza Jalali Naeini; Shahbod Seighalani (برنامه‌ریزی و بودجه, 2023)
Two major sources of inflationary forces in Iran's economy during the past three decades have been the exchange rate depreciation and soaring imported goods prices, and the imbalance between the nominal scale of the economy and its production capacity. In the period of 2012-2022, the main cause for exchange rate depreciation and the most important driver of cost upsurge was the international sanctions. In this period, the demand-side policies, specifically monetary policy, were reactive and could not restrain inflationary pressures emanating from the foreign shocks. In contrast, during the period 2001-2011, fiscal and monetary expansions led to aggregate demand expansion, however, due to the stability of the exchange rate and the supply chains, inflation remained relatively in check over the medium run. The stability of the nominal exchange rate also increased the demand for Rial as a financial asset thereby absorbing growth in M2. The average annual growth rate of M2 in the decade of sanctions (2012-2022) was two and a half percent higher than the previous decade, but the average annual inflation rate was nearly fourteen percent higher. After re-imposition of sanctions by the USA in 1998, the average annual inflation rate rose to above 42% and remained significantly higher than the long-term trend. According to the findings of this paper, the difference in output and inflation during the last two decades can be attributed to the occurrence of external shocks and their impact on the cost of production and on the supply chain.